2022
DOI: 10.1038/s41746-022-00729-z
|View full text |Cite
|
Sign up to set email alerts
|

An interpretable artificial intelligence system for detecting risk factors of gastroesophageal variceal bleeding

Abstract: Bleeding risk factors for gastroesophageal varices (GEV) detected by endoscopy in cirrhotic patients determine the prophylactical treatment patients will undergo in the following 2 years. We propose a methodology for measuring the risk factors. We create an artificial intelligence system (ENDOANGEL-GEV) containing six models to segment GEV and to classify the grades (grades 1–3) and red color signs (RC, RC0-RC3) of varices. It also summarizes changes in the above results with region in real time. ENDOANGEL-GEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Two multicenter studies in China investigated the value of AI in efforts to detect gastroesophageal varices. 48,49 Their results showed that, in the detection of gastroesophageal varices, AI and physicians demonstrated comparable accuracy. Furthermore, in the diagnosis of bleeding risk factors such as the red color sign, AI demonstrated diagnostic ability superior to physicians.…”
Section: Applications Of Ai In the Detection Of Gastroesophageal Varicesmentioning
confidence: 97%
See 1 more Smart Citation
“…Two multicenter studies in China investigated the value of AI in efforts to detect gastroesophageal varices. 48,49 Their results showed that, in the detection of gastroesophageal varices, AI and physicians demonstrated comparable accuracy. Furthermore, in the diagnosis of bleeding risk factors such as the red color sign, AI demonstrated diagnostic ability superior to physicians.…”
Section: Applications Of Ai In the Detection Of Gastroesophageal Varicesmentioning
confidence: 97%
“…Finally, the AI model provided appropriate treatment recommendations based on the current test results. 48,49…”
Section: Applications Of Ai In Upper Gastrointestinal Tract Lesion De...mentioning
confidence: 99%
“…Machine learning algorithms, neural networks, and radiomics are fast-paced developing fields in medicine that, year after year, are showing promising results, especially in imaging interpretation. The creation of new software in detecting esophageal varices has shown comparable results with endoscopic findings; even though large-scale studies are still needed, an artificial intelligence called ENDOANGEL-GEV outperformed many endoscopist findings [ 47 , 48 ]. Several other software programs are still in development, but some neural network systems demonstrated comparable results with endoscopy predicting bleeding episodes [ 49 ].…”
Section: Reviewmentioning
confidence: 99%
“…The creation of new software in detecting esophageal varices has shown comparable results with endoscopic findings; even though large-scale studies are still needed, an artificial intelligence called ENDOANGEL-GEV outperformed many endoscopist findings [ 47 , 48 ]. Several other software programs are still in development, but some neural network systems demonstrated comparable results with endoscopy predicting bleeding episodes [ 49 ]. Machine learning algorithms have taken the spotlight on predicting high-risk esophageal varices.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation